Radiation stability of natural aluminosilicates various structural types by electrons and gamma quantium - Dikiy, N.P.; Bereznyak, O.P.; Lyashko, Yu.V.; Medvedeva, O.P.; Medvedev, D.V. (Problems of Atomic Science and Technology, 2023)
The analysis of the properties of natural aluminosilicates in the conditions of various physical loadings and thermal factors are carred out. Microcline and clinoptilolite are inorganic materials having sorption opportunities to radionuclides. It is shown that under the effects of electrons, gamma quanta and thermal factors in natural aluminosilicates of various structures take place different radioaction stimulation of transformation which can be using for future perspective developments. Проведено аналіз властивостей природних алюмосилікатів в умовах дії різних фізичних навантажень та термальних факторів. Мікроклін та кліноптилоліт ‒ неорганічні матеріали, які мають сорбційні можливості до радіонуклідів. Показано, що під впливом електронів, гамма-квантів та термальних факторів у природних алюмосилікатах різної структури виникають різноманітні радіаційно-стимульовані трансформації, які можуть бути використані для майбутніх перспективних розробок.